2023
DOI: 10.3390/brainsci13040550
|View full text |Cite
|
Sign up to set email alerts
|

Articulation-Function-Associated Cortical Developmental Changes in Patients with Cleft Lip and Palate

Abstract: Cleft lip and palate (CLP) is one of the most common craniofacial malformations. Overall, 40–80% of CLP patients have varying degrees of articulation problems after palatoplasty. Previous studies revealed abnormal articulation-related brain function in CLP patients. However, the association between articulation disorders and cortical structure development in CLP patients remains unclear. Twenty-six CLP adolescents (aged 5–14 years; mean 8.88 years; female/male 8/18), twenty-three CLP adults (aged 18–35 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…Chen's team has systematically evaluated the influence of speech therapy on patients with NSCLP. Their findings showed that an underlying structural and functional alteration in the brain might lead to speech and language dysfunction in patients with NSCLP [13][14][15][16]. While previous studies have revealed potential associations between structural and functional brain abnormalities related to cleft palate speech, they have not fully elucidated the neural mechanisms that underlie the development of cleft-related speech.…”
Section: Introductionmentioning
confidence: 99%
“…Chen's team has systematically evaluated the influence of speech therapy on patients with NSCLP. Their findings showed that an underlying structural and functional alteration in the brain might lead to speech and language dysfunction in patients with NSCLP [13][14][15][16]. While previous studies have revealed potential associations between structural and functional brain abnormalities related to cleft palate speech, they have not fully elucidated the neural mechanisms that underlie the development of cleft-related speech.…”
Section: Introductionmentioning
confidence: 99%